Population and sexual fluctuation of Calliphoridae and Mesembrinellidae (Diptera: Oestroidea) in the Atlantic forest of Rio de Janeiro - Mariana dos Passos Nunes; Wellington Thadeu de Alcantara Azevedo; Alexandre Sousa da Silva; Jeronimo Alencar; Cláudia Soares Santos Lessa; Valéria Magalhães Aguiar (PLoS ONE, 2025)
Dipterans of the Calliphoridae and Mesembrinellidae families are of high relevance in the Atlantic Forest of Rio de Janeiro, and it is important to examine their diversity and abundance in the different ecological areas of this biome over a time interval. This study aimed to study the diversity and abundance of Calliphoridae and Mesembrinellidae by evaluating the sexual variation and the influence of abiotic factors (average temperature, relative humidity and total precipitation) on the capture of insects collected during the four seasons of the year. Four traps were installed in each ecological area containing 300 grams of beef liver as attractive bait, which remained exposed for 48 hours in each season during the period between autumn 2021 and summer 2022. The collected dipterans were sacrificed, sent to the Laboratório de Estudos de Dípteros (LED-UNIRIO), and taxonomically identified. The Kruskal-Wallis and Wilcoxon tests were used to examine the influence of the four seasons on the abundance, and the Spearman correlation was used to relate abundance to abiotic variables. A total of 2,826 dipterans were collected during the four seasons of the year, represented by nine species of the Calliphoridae family and ten of the Mesembrinellidae family. During the summer, a numerically larger amount of insects was collected, but the Kruskal-Wallis test (chi-square = 5.2781, p = 0.1525) showed there was no significant difference between the abundance of the species collected and the seasons. Spearman’s correlation showed that most species did not show a significant correlation between their respective abundances and the analyzed abiotic factors. The Wilcoxon test indicated that there is a significant difference between the abundance of females and males, with females being significantly more abundant than males, however the difference is statistically greater within the Calliphoridae family (W = 60.49, p = 5.8x10-12) in relation to the Mesembrinellidae family (W = 1231.5, p = 0.019).